The Influence of Using Module with Computational Thinking Unplugged Approaches and Module with Scientific Approaches Based on Student's Critical Thinking Ability Towards Cognitive Ability the Subject of Temperature and Heat Transfer - Fauzi, Ahmad; Zahroh, Shofi Hikmatuz; Ekawati, Elvin Yusliana (Widyagogik, 2022)
The purpose of this research was to determine (1) the difference effect between the use of module with an unplugged computational thinking approach and module with a scientific approach to students' cognitive abilities on the subject of temperature and heat transfer, (2) the differences effect of students' critical thinking abilities in the high and low category on students' cognitive abilities on the subject of temperature and heat transfer, (3) the interaction between the effect of using module with a computational thinking unplugged approach and module with a scientific approach and students' critical thinking skills on students' cognitive abilities on the subject of temperature and heat transfer. This research used a quasi-experimental method with a 2x2 factorial design. The population in this research were all students of the first semester of physics education at Universitas Sebelas Maret. Data collection techniques used are tests and questionnaires. Data were analyzed using a two-way ANOVA with different cell contents. The results of the study show that: (1) there is a difference in the effect between the use of module with a computational thinking unplugged approach and module with a scientific approach to students' cognitive abilities on the subject of temperature and heat transfer ( 2) there is a difference in the effect of students' critical thinking skills in the high and low categories on students' cognitive abilities on the subject of temperature and heat transfer, and (3) there is no interaction between the effect of using module with a computational approach thinking unplugged and module with a scientific approach and students' critical thinking skills on students' cognitive abilities on the subject of temperature and heat transfer.